2011
DOI: 10.1007/s10903-011-9481-6
|View full text |Cite
|
Sign up to set email alerts
|

A Community Intervention: AMBER: Arab American Breast Cancer Education and Referral Program

Abstract: Although the number of Arab Americans is growing in the United States, there is very little data available on this population's cancer incidence and screening practices. Moreover, there are few interventions addressing their unique needs. This study aims to determine effective strategies for increasing breast cancer screening in at-risk underserved Arab American women. AMBER utilizes a community based participatory approach to conduct formative research and program interventions, including culturally appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Consistent with Kleinman’s explanatory model of health, illness and disease, this study found that several complex beliefs and attitudes toward breast cancer screening influence BCS uptake among Arabic-speaking women in Qatar. As with Arab or Muslim women living in the West, the women interviewed had low BCS awareness and low screening rates, they overwhelmingly preferred female physicians, and they gave fear or embarrassment as reasons for why they did not plan to have a CBE or mammogram [40,41]. However, the majority of participants wanted to know if they have cancer, would make a mammogram appointment if advised to, and trusted their physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with Kleinman’s explanatory model of health, illness and disease, this study found that several complex beliefs and attitudes toward breast cancer screening influence BCS uptake among Arabic-speaking women in Qatar. As with Arab or Muslim women living in the West, the women interviewed had low BCS awareness and low screening rates, they overwhelmingly preferred female physicians, and they gave fear or embarrassment as reasons for why they did not plan to have a CBE or mammogram [40,41]. However, the majority of participants wanted to know if they have cancer, would make a mammogram appointment if advised to, and trusted their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Because the State of Qatar provides gender-appropriate HCPs in most hospitals and health centers, concerns about HCP gender may be a perceived barrier that can be alleviated with greater awareness of health care services that are culturally and religiously compliant with most Arab women’s beliefs. Including religious leaders as part of awareness campaigns aimed at promoting BCS as being congruent with Islamic principles should be an essential part of a culturally appropriate intervention strategy, and has been found to increase the rate of awareness and success of intervention programs for Arab or Muslim women [40,41]. Arab breast cancer survivors can also play an important role in communicating that breast cancer is a chronic disease rather than a fatal one.…”
Section: Discussionmentioning
confidence: 99%
“…This review employed the following inclusion criteria: (1) the study provided an evaluation or description of a BCS program/educational intervention for Arabic women living in an Arabic region or in a Western multicultural society, (2) the study involved experimental, quasi-experimental, or longitudinal design, (3) the study sought to improve breast cancer knowledge and/or BCS rates in Arabic women. We defined Arabic women as women who speak Arabic and who live in Arab countries in the Middle East or North Africa, or Arab Americans and their descendants [ 38 , 39 ]. Exclusion criteria were studies that evaluated breast self-examinations, nonintervention studies, biomedical/treatment research, pharmaceutical research, descriptive research, instrumental research, and studies that did not report valid outcome measures.…”
Section: Methodsmentioning
confidence: 99%
“…This is perhaps due to the scant number of interventions conducted among Arab populations. Moreover, in the United States, Arab Americans are often grouped with Caucasians according to the United States Office of Management and Budget; therefore, accessing detailed data on the Arabic population is difficult [ 23 , 38 , 39 ]. The present review updates current knowledge on the effectiveness of existing interventions designed to increase BCS in Arabic populations in Arabic countries and North America and aims to improve the development of effective intervention programs that promote BCS among Arabic women living in Qatar.…”
Section: Introductionmentioning
confidence: 99%
“…Although religious guidelines allow Muslim women to take care of their health, and have their bodies examined by health care professionals for medical reasons, [31] there is strong preference for a female health professional. [32,33] The reason could be the objection raised by their husbands or male relatives to breast examination as males are considered the guardians of the females in middle east. [34] Lastly, in KSA, the women are caretakers and tend to spend all their time focusing on the needs of family members before they focus on their own health needs.…”
Section: Sufficient Insufficientmentioning
confidence: 99%